Anaerobic Threshold Biophysical Characterisation of the Four Swimming Techniques - Carvalho, Diogo Duarte; Soares, Susana; Zacca, Rodrigo; Sousa, João; Marinho, Daniel Almeida; Silva, António José; Vilas-Boas, João Paulo; Fernandes, Ricardo J. (International Journal of Sports Medicine, 2020)
The anaerobic threshold (AnT) seems to be not only a physiologic boundary but also a transition after which swimmers technique changes, modifying their biomechanical behaviour. We expanded the AnT concept to a biophysical construct in the four conventional swimming techniques. Seventy-two elite swimmers performed a 5×200 m incremental protocol in their preferred swimming technique (with a 0.05 m·s−1 increase and a 30 s interval between steps). A capillary blood samples were collected from the fingertip and stroke rate (SR) and length (SL) determined for the assessment of [La], SR and SL vs. velocity inflexion points (using the interception of a pair of linear and exponential regression curves). The [La] values at the AnT were 3.3±1.0, 3.9±1.1, 2.9±1 .34 and 4.5±1.4 mmol·l−1 (mean±SD) for front crawl, backstroke, breaststroke and butterfly, and its corresponding velocity correlated highly with those at SR and SL inflection points (r=0.91–0.99, p<0.001). The agreement analyses confirmed that AnT represents a biophysical boundary in the four competitive swimming techniques and can be determined individually using [La] and/or SR/SL. Blood lactate increase speed can help characterise swimmers’ anaerobic behaviour after AnT and between competitive swimming techniques.
Keywords: physiology; biomechanics; biophysics; anaerobic threshold; elite swimmers